Bacterial community dynamics during cold storage of minced meat packaged under modified atmosphere and supplemented with different preservatives. (June 2015) - Stoops, J.; Ruyters, S.; Busschaert, P.; Spaepen, R.; Verreth, C.; Claes, J.; Lievens, B.; Van Campenhout, L.
Abstract: Since minced meat is very susceptible for microbial growth, characterisation of the bacterial community dynamics during storage is important to optimise preservation strategies. The purpose of this study was to investigate the effect of different production batches and the use of different preservatives on the composition of the bacterial community in minced meat during 9 days of cold storage under modified atmosphere (66% O2, 25% CO2 and 9% N2 ). To this end, both culture-dependent (viable aerobic and anaerobic counts) and culture-independent (454 pyrosequencing) analyses were performed. Initially, microbial counts of fresh minced meat showed microbial loads between 3.5 and 5.0 log cfu/g. The observed microbial diversity was relatively high, and the most abundant bacteria differed among the samples. During storage an increase of microbial counts coincided with a dramatic decrease in bacterial diversity. At the end of the storage period, most samples showed microbial counts above the spoilage level of 7 log cfu/g. A relatively similar bacterial community was obtained regardless of the manufacturing batch and the preservative used, with Lactobacillus algidus and Leuconostoc sp. as the most dominant microorganisms. This suggests that both bacteria played an important role in the spoilage of minced meat packaged under modified atmosphere. Highlights: Culture-dependent and independent analyses were used to assess microbial quality. During storage, microbial counts increased while the bacterial diversity decreased. Lactobacillus algidus and Leuconostoc sp. were the dominant bacteria. Different batches and preservatives resulted in a similar bacterial community.